1997
DOI: 10.1021/bi962502o
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of Distal Residues of Horseradish Peroxidase:  Influence on Substrate Binding and Cavity Properties

Abstract: The manner in which the distal heme pocket residues of peroxidases control the reaction mechanism and ligand binding has been investigated further by analysis of the electronic absorption and resonance Raman (RR) spectra of distal site mutants of recombinant horseradish peroxidase (HRP-C*). The roles of the conserved distal histidine and arginine residues, particularly in the context of the catalytic mechanism originally proposed for cytochrome c peroxidase (CCP), have been evaluated by studying the His42 --> … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
106
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(132 citation statements)
references
References 40 publications
25
106
1
Order By: Relevance
“…However, when peroxidase activity is measured with two standard peroxidase substrates, ABTS and a tyrosine derivative, the peroxidase activity of CeDUOX1 1-589 is found to be much lower than that of LPO. This lower activity is consistent with the absence of a distal histidine residue that is critical for the high activity of most peroxidases (42)(43)(44)(45)(46)). However, a low level of activity for the CeDUOX1 peroxidase domain may be desirable in the context of its function in the intact organism.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…However, when peroxidase activity is measured with two standard peroxidase substrates, ABTS and a tyrosine derivative, the peroxidase activity of CeDUOX1 1-589 is found to be much lower than that of LPO. This lower activity is consistent with the absence of a distal histidine residue that is critical for the high activity of most peroxidases (42)(43)(44)(45)(46)). However, a low level of activity for the CeDUOX1 peroxidase domain may be desirable in the context of its function in the intact organism.…”
Section: Discussionsupporting
confidence: 69%
“…It has been shown through site-specific mutagenesis that the distal catalytic histidine in peroxidases is crucial to their activity. When mutated in such enzymes as horseradish peroxidase, cytochrome c peroxidase, and dehaloperoxidase, a significant loss of activity is observed (42)(43)(44)(45)(46). This fact has led researchers to postulate that the N-terminal region of DUOX1 may not act as a classical peroxidase but rather as a SOD (8,12).…”
Section: Design and Expression Of Soluble Duox1mentioning
confidence: 99%
“…Whereas a water-ligated 6c/HS structure is a major species in the T66V mutant similar to WT cAOS, a 5c/HS species was observed as a minor component in the T66V mutant. The fact that the water coordination to the heme iron was stabilized by a hydrogen bond and/or a negatively charged group in other heme proteins (41)(42)(43) suggests that the mutation of Thr-66 possibly affects the distal environment. Furthermore, the CN affinity was increased to 8-fold of that of WT cAOS by the mutation, which also provides evidence for the structural perturbation at the heme distal site upon the mutation.…”
Section: Discussionmentioning
confidence: 99%
“…7b). The distance between heme (Fe) and catalytic water molecule is 2.65 Å which is the same as in case of HRP and is enough to control the electronic structure of heme system (Howes et al 1997). Crystallographic study has revealed that BHA was found at the peroxidase catalytic site, whereas hydrophobic residues are present near the aromatic portion of the substrate (Henriksen et al 1998b).…”
Section: Substrate Binding and The Role Of Active Site Residuesmentioning
confidence: 99%